Comparison of polarization at two lunar eclipse events. (9th March 2019) - Takahashi, Jun; Itoh, Yoichi; Watanabe, Makoto; Akitaya, Hiroshi; Takaki, Katsutoshi; Kawabata, Koji S; Itoh, Ryosuke; Oasa, Yumiko
Abstract: We present the results of imaging polarimetry of the eclipsed Moon on 2014 October 8. The observed polarization degree was less than 1% in both the V and R bands, which contrasts with the reported 2%–3% polarization during the eclipse of 2015 April 4. We examined the Earth's atmospheric data on the two dates and found that the high (≥7 km) cloud distribution was more inhomogeneous for the 2015 eclipse than it was for the 2014 eclipse. The polarization position angle observed during the 2015 eclipse can be explained if the major polarizing source was high clouds with an intermediate horizontal optical thickness. We suggest a possible dependence of the lunar eclipse polarization on the Earth's high cloud distribution.